Exercise intensities modulate cognitive function in spontaneously hypertensive rats through oxidative mediated synaptic plasticity in hippocampus. Issue 17 (30th July 2021) - Lee, Cheng‐Che; Wu, De‐Yu; Chen, Syue‐yi; Lin, Yi‐Pin; Lee, Tsung‐Ming
Abstract: Oxidative damage in the brain may lead to cognitive impairments. There was considerable debate regarding the beneficial effects of physical exercise on cognitive functions because exercise protocols have varied widely across studies. We investigated whether different exercise intensities alter performance on cognitive tasks. The experiment was performed on spontaneously hypertensive rats (6 months at the established phase of hypertension) distributed into 3 groups: sedentary, low‐intensity exercise and high‐intensity exercise. Systolic blood pressure measurements confirmed hypertension in spontaneously hypertensive rats. In comparison to normotensive Wistar‐Kyoto rats, sedentary spontaneously hypertensive rats had similar escape latencies and a similar preference for the correct quadrant in the probe trial. Compared to the sedentary group, the low‐intensity exercise group had significantly better improvements in spatial memory assessed by Morris water maze. Low‐intensity exercise was associated with attenuated reactive oxygen species, as measured by dihydroethidine fluorescence and nitrotyrosine staining in the dentate gyrus of the hippocampus. This was coupled with increased numbers of neurons and dendritic spines as well as a significant upregulation of synaptic density. In contrast, the beneficial effects of low‐intensity exercise are abolished in high‐intensity exercise as shown by increased free radical levels and an impairment in spatial memory. We concluded that exercise is an effective strategy to improve spatial memory in spontaneously hypertensive rats even at an established phase of hypertension. Low‐intensity exercise exhibited better improvement on cognitive deficits than high‐intensity exercise by attenuating free radical levels and improving downstream synaptic plasticity.